The Effective use of praise in teaching adults - Skalecká, Kamila (Univerzita Pardubice, 2010)
This bachelor paper was aimed at the effective use of praise in teaching adults. The introductory part focused on defining the term of praise in its elementary sense together with three different approaches that can be taken account to when praising and that were behaviorist, humanistic and social-constructivist. The theoretical part was concluded by defining the age group of adults and its specifics with a view to teaching. By means of action research and the methods of observation and interviewing, the practical part introduced research aimed to find out how the adult students are influenced by praise and in what ways the praise is used and how it is perceived. The collected data were analysed in order to find out how to use praise effectively in future. Final part of this paper summarizes the features and steps for using praise with individual students, which would be the most effective for them.
Pochvala a její efektivní využívání při výuce dospělých
Keywords: pochvala; andragogika; akční výzkum; praise; andragogy; action research